2006
DOI: 10.1021/bm060251l
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Permeability on Aqueous Biopolymer Interfaces in Spinning Drop Experiments

Abstract: In this paper we show that interfaces in aqueous phase-separated biopolymer mixtures are permeable for all components present in the system. In spinning drop experiments, droplets of the low-density phase decreased up to 90% in volume over a time span of days to weeks, when inserted in a matrix of the high-density phase. We propose an expression for this change of volume in time in terms of diffusion coefficients of the components. From the magnitude of these coefficients, we conclude that the transfer of gela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
26
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 20 publications
3
26
0
Order By: Relevance
“…However, it was recently reported that the centrifugal field that is applied in this method, significantly affects the compositions of coexisting liquid phases. Demixed systems can even be brought into the one-phase regime [4].The method that is presented in this Letter does not rely on optical contrast, density differences, or strong external fields. We use colloidal probe atomic force microscopy (CP-AFM), introduced independently by Ducker et al [5] and Butt [6], to measure equilibrium forces originating from capillary, liquid bridges between two surfaces.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was recently reported that the centrifugal field that is applied in this method, significantly affects the compositions of coexisting liquid phases. Demixed systems can even be brought into the one-phase regime [4].The method that is presented in this Letter does not rely on optical contrast, density differences, or strong external fields. We use colloidal probe atomic force microscopy (CP-AFM), introduced independently by Ducker et al [5] and Butt [6], to measure equilibrium forces originating from capillary, liquid bridges between two surfaces.…”
mentioning
confidence: 99%
“…However, it was recently reported that the centrifugal field that is applied in this method, significantly affects the compositions of coexisting liquid phases. Demixed systems can even be brought into the one-phase regime [4].…”
mentioning
confidence: 99%
“…That mass transfer can have an appreciable effect on the dynamic behavior of a deformed droplet was also shown in recent interfacial tension measurements of biopolymer solutions, using the spinning drop method [6]. Droplets deformed by spinning the capillary, slowly dissolved, and the rate of dissolution increased with increasing spinning rate, or increasing deformation of the droplets.…”
mentioning
confidence: 52%
“…In these systems water and dissolved molecules can transfer easily from one aqueous bulk phase to the other. This high permeability of the interface has a significant effect on the stressdeformation and deformation-relaxation behavior of, for example, droplets in phase-separated biopolymer solutions [4,5].That mass transfer can have an appreciable effect on the dynamic behavior of a deformed droplet was also shown in recent interfacial tension measurements of biopolymer solutions, using the spinning drop method [6]. Droplets deformed by spinning the capillary, slowly dissolved, and the rate of dissolution increased with increasing spinning rate, or increasing deformation of the droplets.…”
mentioning
confidence: 69%
See 1 more Smart Citation